PENGEMBANGAN SDM DALAM PENGELOLAAN DESA WISATA MELALUI SERTIFIKASI KOMPETENSI KEPEMANDUAN OUTBOND DI DESA WISATA JAKA GARONG - Eisya Alaida Pratiwi; Muhammad Salisul Khakim (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2025)
Human Resource Development (HRD) through outbound guide competency certification in Tourism Villages has a crucial role in improving service quality, competitiveness, and sustainability in village economic development. Outbound guide certification plays an important role in improving the professionalism of guides and building tourist trust in tourist destinations. The purpose of this study was to understand and analyze the outbound guide competency certification program and how to evaluate the follow-up of the outbound guide competency certification program. This study was conducted using a descriptive qualitative method, using observation, interviews, and documentation as the main tools in collecting data. The results obtained indicate that the outbound guide certification program in Jaka Garong Tourism Village has succeeded in significantly developing the potential of human resources (HR). This program not only improves the discipline and technical skills of the guides, but also strengthens teamwork, work enthusiasm, and visitor satisfaction. Indicators of the success of this program can be seen from the decrease in accident rates, efficiency of resource use, and improvement in the quality of services provided. However, to maintain the sustainability of the program, it is recommended to adjust the learning method to be more practice-based. In addition, managers can expand the scope of training by including materials related to advanced risk management, outbound activity innovation, and interpersonal skills development. With this approach, Jaka Garong Tourism Village can continue to develop into a safe, attractive, and highly competitive tourist destination.